Grassland rehabilitation after alien invasive tree eradication: landscape degradation and sustainability in rural Eastern Cape - Okoye, Perpetua Ifeoma (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.